Everyday Human Cognition and Behaviour. - Kingstone, Alan (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2020)
When laboratory studies lose touch with real world context, they may generate fundamental misunderstandings of the principles of human cognition, behaviour, and associated brain processes. This article describes how this can occur, and proposes an alternative research approach--cognitive ethology--that enables researchers to link cognitions and behaviours as they operate in everyday life, with those studied in controlled, lab-based investigations.